Biosensors – basics and use (International Journal of Biology and Chemistry, 2014)
The work is devoted to the existing variety of biosensors used to control environmental pollution. The physical principles of enzymatic, microbial and DNA sensors are reviewed. It is concluded that it is possible to create biosensors based on Drosophila melanogaster genetic constructs, with the similar properties to microbiological ones.